Ultra-short-process high-quality leather making method and made leather

By pre-drying raw materials during the leather making process, using Tween-containing ethanol solution and long-chain silane coupling agent, and performing low-temperature drying, the problems of cumbersome processes, high costs and insufficient leather strength in the leather making technology are solved, and efficient, low-cost and high-quality leather production is achieved.

CN119530466AActive Publication Date: 2025-02-28SICHUAN UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411917244.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-02-28
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The current leather making technology has problems such as cumbersome production processes, long-term, high cost and insufficient leather strength, which is difficult to meet the market's demand for efficient, low-cost and high-quality leather.

Method used

The ultra-short process high-quality leather making method was adopted, and the raw materials were pre-dried to the moisture content of 21 wt%-40 wt%, and the Tween-containing ethanol solution was infiltrated, and then the pressure was extruded with a long-chain silane coupling agent, and finally the low-temperature drying was carried out.

Benefits of technology

It significantly reduces solvent consumption and chemical materials costs, reduces energy consumption, simplifies the leather process, improves production efficiency, and improves the softness, fullness and strength of the leather.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of leather processing, and discloses an ultra-short-process high-quality leather making method and made leather, bare leather or tanned leather or crust leather is used as a raw material, after pre-drying treatment is conducted, an ethanol solution containing Tween is adopted for infiltration, after extrusion, a long-chain silane coupling agent is used for treatment, and finally low-temperature drying is conducted. The core of the invention lies in that the Tween can effectively inhibit the hydrolysis reaction of the silane coupling agent when the moisture content of the leather blank is 21-40%, prevent the silane coupling agent from being converted into high-activity silanol too early, and ensure that the silane coupling agent can uniformly and deeply permeate into the leather. Subsequently, by applying a relatively mild temperature condition (20-50 DEG C), under the assistance of a proper amount of water, the binding reaction of the silane coupling agent and the leather collagen is efficiently and sufficiently performed. According to the innovative method, the leather making efficiency can be improved, the strength parameter of the leather is remarkably improved, the leather processing target of high efficiency, energy conservation and controllable cost is achieved, and revolutionary technical progress is brought to the leather making industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of leather processing, in particular to an ultra-short process high-quality leather making method and the made leather. Background Art

[0002] As a key component of light industry, the leather industry not only inherits a rich craft heritage, but also plays an indispensable role in modern life. The industry provides consumers with a wide range of leather products, including daily shoes and clothing as well as high-end furniture decorations, which greatly improves people's quality of life and meets diversified market demands. However, current leather technology faces two major challenges: first, processing delimed bare skin into finished leather requires multiple complex steps such as softening, pickling, tanning, neutralization, retanning, dyeing and fatliquoring. This process is cumbersome and time-consuming, which seriously affects the improvement of production efficiency; second, a large amount of tanning agents and dyeing and finishing materials are used in the processing process, which not only increases the cost, but also the strength of the final product often fails to meet the expected standards even with huge investment. In view of this, in order to promote the sustainable and healthy development of the leather industry and enhance the market competitiveness of leather products, it is urgent to develop an efficient leather technology that can simplify the production process, reduce manufacturing costs and ensure that the leather has high strength performance.

[0003] Chinese patent CN115747388A "A method for manufacturing metal-free leather by hydrophobic modification and the leather products obtained" and Chinese patent CN113061670A "Superhydrophobic modification method of substances containing leather collagen fibers and tanning agent-free leather making method and leather products" disclose a method for preparing leather by hydrophobic modification of dehydrated leather blanks using long-chain silane coupling agents. This method significantly simplifies the leather making process, but faces two major challenges in practical application. First, a large amount of solvent is required for dehydration before treatment with long-chain silane coupling agents, and the moisture content of the leather blanks is strictly controlled between 4wt%-20wt%. This step significantly increases solvent consumption and chemical costs, which is not conducive to the effective control of production costs; secondly, the leather blanks treated with long-chain silane coupling agents need to be further treated under high temperature conditions of 60-160°C to promote the combination of coupling agents and leather collagen fibers. This process is not only energy-intensive, but also has high requirements for production equipment. These factors severely limit the application and promotion of leather making technology based on long-chain silane coupling agents in industry.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] In order to solve the problems in the background technology, the present invention aims to provide a more efficient, energy-saving and cost-controlled ultra-short process high-quality leather making method and leather products. The process is simple to operate and easy to implement, and the leather produced is soft, plump and high in strength.

[0006] In order to achieve the above purpose, the technical solution adopted by the present invention is: The ultra-short process high-quality leather making method uses bare leather, tanned leather or crust leather as raw materials, pre-drying the raw materials to a moisture content of 21wt%-40wt%, then soaking them with an ethanol solution containing Tween, extruding them, treating them with a long-chain silane coupling agent, and finally drying them at low temperature; Wherein, based on the weight of the raw materials, the amount of Tween added is 0.1wt%-1wt%, the amount of ethanol added is 50wt%-200wt%; the long-chain silane coupling agent is C n H 2n+1 (CH3) 3-m SiX m , n is an integer between 6 and 18, and X is a group that can be hydrolyzed into a silanol.

[0007] Preferably, X includes any one of a chloro group, a methoxy group and an ethoxy group.

[0008] Preferably, the addition amount of the long-chain silane coupling agent is 2wt%-18wt% of the weight of the raw material.

[0009] Preferably, the low-temperature drying temperature is 20-50°C.

[0010] Preferably, the bare skin comprises any one of delimed bare skin, softened bare skin, pickled bare skin and bare skin obtained by pickling-depickling process.

[0011] Preferably, the tanned leather comprises any one of chrome tanned leather, aluminum tanned leather, zirconium tanned leather, zeolite tanned leather, multi-metal tanning agent tanned leather, vegetable tanned leather, aldehyde tanned leather, phenolic synthetic tanning agent tanned leather and active chlorine tanned leather.

[0012] Preferably, the crust leather is obtained by performing at least one of the processes of retanning, dyeing and fatliquoring.

[0013] Preferably, the pre-dried raw material is soaked in an ethanol solution containing Tween for 5-120 min.

[0014] Preferably, the treatment method using a long-chain silane coupling agent is: applying an ethanol solution of the long-chain silane coupling agent to the flesh surface of the skin blank by rotating a drum, brushing, rolling or spraying for 0.5-60 min.

[0015] The invention also discloses leather obtained by adopting any of the above ultra-short process high-quality leather making methods.

[0016] Compared with the prior art, the present invention has the following beneficial effects: (1) Significantly reduce solvent consumption and chemical material costs: The method of the present invention reduces the dependence on large amounts of solvents and reduces the requirements for the degree of dehydration of the crust, thereby significantly reducing solvent consumption and chemical material costs, bringing significant advantages to production cost control.

[0017] (2) Reduce energy consumption and avoid equipment upgrades: The present invention realizes the effective combination of long-chain silane coupling agents with skin collagen at a low temperature of 20-50°C, which significantly reduces energy consumption. Existing equipment can meet mild drying conditions, avoiding additional equipment investment.

[0018] (3) Simplifying the leather making process and improving production efficiency: Compared with the multi-step operations such as retanning, dyeing and fatliquoring in the traditional leather making process, the method of the present invention shows extremely high simplification, greatly shortening the leather making process, thereby significantly improving production efficiency.

[0019] (4) Improving leather quality and application scope: Leather prepared by traditional technology often has poor strength, while the method of the present invention not only gives leather excellent strength characteristics, but also ensures its soft and plump texture. This makes the method of the present invention suitable for processing various types of leather, effectively broadening the scope of application and improving product value. DETAILED DESCRIPTION

[0020] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is described in detail below in conjunction with specific implementation cases and references. It should be pointed out that the following actual cases are only further detailed descriptions of the present invention and do not limit the protection scope of the present invention. Relevant technicians can still make some non-essential improvements and adjustments based on the research content of the present invention.

[0021] In the traditional process, before using long-chain silane coupling agents to treat leather blanks, the moisture content of the leather blanks must be strictly controlled to 20wt% or less with the help of a large amount of solvents. The reason is that long-chain silane coupling agents are easily hydrolyzed into silanols when they come into contact with water, resulting in a sharp increase in reaction activity, and then quickly combine with leather collagen and deposit on the surface of the leather, which not only limits the in-depth effect of the coupling agent, but also affects the uniformity of the treatment effect. When the long-chain silane coupling agent penetrates into the leather, its reaction activity with leather collagen decreases in a low moisture environment, so high temperature (60-160℃) conditions are required to accelerate the reaction process. It can be seen that whether it is the use of a large amount of solvents during dehydration or the promotion of reaction at high temperature, both have high requirements for chemical material costs and energy consumption costs, which is not conducive to industrial production. It should be noted that when controlling the moisture content in the leather blank, although non-solvent treatment methods such as vacuum drying can also be used to make its moisture content at 20wt% or less, these drying methods will cause the fibers in the leather blank to bond and the silane coupling agent cannot penetrate.

[0022] The embodiment of the present invention provides an ultra-short process high-quality leather making method, which uses bare leather, tanned leather or crust leather as raw materials, pre-drying the raw materials to a moisture content of 21wt%-40wt%, then soaking them with an ethanol solution containing Tween, extruding them, treating them with a long-chain silane coupling agent, and finally drying them at low temperature; Wherein, based on the weight of the raw materials, the amount of Tween added is 0.1wt%-1wt%, and the amount of ethanol added is 50wt%-200wt%; The long-chain silane coupling agent is C n H 2n+1 (CH3) 3-m SiX m , n is an integer between 6 and 18, and X is a group that can be hydrolyzed into a silanol.

[0023] The embodiment of the present invention does not need to rely on a large amount of solvent for dehydration treatment, nor does it need a leather making method that promotes reaction at high temperature. This breakthrough is due to the use of an ethanol solution containing Tween for infiltration. In this infiltration process, a small amount of Tween can achieve multiple effects at the same time: on the one hand, since Tween molecules are rich in multiple hydroxyl functional groups, these hydroxyls can effectively inhibit the hydrolysis reaction of the silane coupling agent, preventing it from being converted into a highly active silanol form prematurely, thereby ensuring that the silane coupling agent can penetrate into the leather evenly and deeply, rather than just depositing on the surface; on the other hand, Tween has a certain hydrophilicity, can control the relative constant moisture in the leather blank, play a certain water retention effect, and stably control the moisture content in the treated leather blank within an appropriate range. The amount of ethanol used is greatly reduced compared to the prior art, and it is difficult to play a dehydrating role. In the embodiment of the present invention, its role is to infiltrate collagen fibers, which is convenient for subsequent silane to penetrate into the leather.

[0024] Once the silane coupling agent is evenly distributed inside the leather, the binding reaction between the silane coupling agent and the leather collagen can be carried out efficiently and fully by applying relatively mild temperature conditions and with the assistance of appropriate amount of water. This optimized reaction environment not only promotes the deep binding of the coupling agent and the leather components, but also significantly improves the treatment effect, ultimately giving the leather products excellent quality and performance, bringing revolutionary technological progress to the leather industry.

[0025] For the appropriate moisture content, the moisture content in the raw material after pre-drying is 21wt%-40wt%. During the infiltration process, Tween can also stabilize the moisture content of the raw material at 21wt%-40wt%, and the collagen fibers in the raw material always remain in a non-bonded state, which is convenient for silane penetration. When the moisture content is lower than 21wt%, although the silane coupling agent can penetrate into the leather, it is difficult to hydrolyze into silanol under low moisture conditions, resulting in low reaction activity. Therefore, the prior art needs to promote the hydrolysis of the silane coupling agent and combine with the leather collagen through high temperature conditions (above 60°C). When the moisture content exceeds 40wt%, Tween cannot effectively inhibit the hydrolysis of the silane coupling agent, that is, the silane coupling agent cannot penetrate into the leather evenly, thus affecting the final effect.

[0026] It should be noted that when the embodiment of the present invention is treated with a silane coupling agent, all long-chain silane coupling agents containing groups that can be hydrolyzed into silanols can achieve the effects of the present invention, for example, including chloro, methoxy and ethoxy groups. This is because the silanols generated by the hydrolysis of these silane coupling agents can form a stable bond with skin collagen to achieve the effects of the present invention. In the prior art, long-chain silane coupling agents are often used to treat the surface of finished leather with hydrophobicity to improve the waterproof and antifouling properties of leather. The embodiment of the present invention realizes the application of long-chain silane coupling agents in the leather preparation process for the first time. Long-chain silane coupling agents, with their unique hydrophobicity, filling and oily properties, can effectively disperse collagen fibers after combining with skin collagen, realize the filling and thickening of the leather blank, and enhance the relative lubricity between collagen fibers. Under the use of Tween, the long-chain silane coupling agent can fully penetrate and stably combine with collagen fibers, which not only gives the finished leather excellent softness and fullness, but also achieves the sensory effects pursued by traditional complex process flows. More importantly, since the use of chemical materials is reduced during the processing process, the chemical components in the finished leather are reduced accordingly, while the fiber component is increased. This change directly promotes a significant improvement in the strength parameters of the finished leather.

[0027] The long-chain silane coupling agent is used for treatment. The commonly used treatment method is: the long-chain silane coupling agent ethanol solution is applied to the skin surface for 0.5-60 minutes by rotating the drum, brushing, rolling or spraying the mixed solution.

[0028] The dosage of the long-chain silane coupling agent is adaptively selected according to the specific effect to be achieved. On the premise that the action principle and effect of the long-chain silane coupling agent have been clearly given above, those skilled in the art can anticipate the effect of the dosage of the long-chain silane coupling agent on the effect. Obviously, if the dosage of the long-chain silane coupling agent is too low, its effect is not significant and the leather performance is poor; if the dosage of the silane coupling agent is too high, not only the cost will increase, but also the leather will have a "plastic feel" and lose some of the excellent sensory properties unique to genuine leather. For reference, the amount of long-chain silane coupling agent added in the embodiment of the present invention is 2wt%-18wt% of the weight of the raw material.

[0029] Since the present invention does not need to control the moisture content of the raw materials to be too low, the moisture content of the raw materials can be kept at 21wt%-40wt% by using a commonly used simple drying process, such as hanging drying, vacuum drying, stretching board drying, nail board drying and pasting board drying. The requirements for the technical indicators and energy consumption indicators of the processing equipment are greatly reduced, and it is particularly suitable for industrial production.

[0030] When the pre-dried raw material is infiltrated with ethanol containing Tween, the infiltration time can be adaptively selected according to the raw material, solution and silane coupling agent dosage, so as to achieve the final leather making effect. For those skilled in the art, after the aforementioned clear role and dosage of each raw material, as well as the mechanism of action of the embodiment of the present invention, the influence of the infiltration time on the final effect can be clearly defined. Obviously, if the infiltration time is too short, sufficient infiltration cannot be achieved; if the infiltration time is too long, ethanol will play a partial dehydrating role, reduce the moisture content in the skin, and is not conducive to the subsequent low-temperature binding of long-chain silane coupling agent and collagen fibers. For reference, in an embodiment of the present invention, the pre-dried raw material is infiltrated with an ethanol solution containing Tween for 5-120 min.

[0031] It should be noted that after soaking with ethanol containing Tween, it is also very important to squeeze out the excess ethanol. Extrusion to remove some of the excess ethanol facilitates the subsequent long-chain silane coupling agent ethanol solution to evenly penetrate into the leather. Specifically, after the extrusion treatment, although a trace amount of ethanol is retained in the leather blank, it is in a relatively ethanol-deficient state as a whole. Under this condition, the long-chain silane coupling agent ethanol solution is applied to the leather blank, and the solution can quickly infiltrate the collagen fibers through capillary action, and the long-chain silane coupling agent can be evenly distributed in the leather in 0.5-60 minutes. If the raw material is not soaked with ethanol containing Tween in advance and squeezed to remove excess ethanol, but Tween, ethanol and long-chain silane coupling agent are directly mixed at the same time to soak the raw material, the long-chain silane coupling agent will not be fully absorbed and evenly distributed in the leather. Therefore, it is necessary to strictly follow the order of "soaking with ethanol containing Tween and squeezing to remove excess ethanol" and then "soaking with long-chain silane coupling agent ethanol solution".

[0032] In general, after extruding, ethanol content is no more than 50wt% in the skin blank. In some preferred embodiments, because conventional extrusion mode is difficult to realize when ethanol content is squeezed to below 15wt% in the skin blank, it is unfavorable for industrial production, so ethanol content can be controlled at 15wt%-50wt% in the skin blank after extrusion. If ethanol content is higher than 50wt%, then cause long-chain silane coupling agent ethanol solution to be difficult to infiltrate collagen fiber by capillary conduction. As can be seen, after extruding, ethanol content can be selected by those skilled in the art from industrialized production cost and actual desired infiltration effect in the skin blank. From the industrial production perspective, the optional conventional extrusion process of the present invention comprises adopting water squeezer or water squeeze stretcher to extrude etc.

[0033] Based on the above theory, the amount of ethanol in the long-chain silane coupling agent ethanol solution can be selectively added according to the desired treatment effect and treatment time. For example, 100 parts by weight of the long-chain silane coupling agent can be dissolved in 100-500 parts by weight of ethanol to obtain the long-chain silane coupling agent ethanol solution.

[0034] The method of applying the long-chain silane coupling agent ethanol solution to the leather blank is a common method of applying a liquid to a solid surface, including drum rotation, brushing, or spraying.

[0035] It should be noted that the leather blank treated with the long-chain silane coupling agent in the embodiment of the present invention does not need to be treated under high temperature conditions of 60-160°C, and can be dried at low temperature, which not only saves the complicated high temperature treatment equipment, but also significantly reduces the processing energy consumption. Obviously, the low temperature in the embodiment of the present invention is defined relative to the high temperature of 60-160°C in the prior art. The present invention can achieve low temperature drying at 20-50°C and significantly improve the performance of leather. Commonly used low temperature drying methods include any one or more of hanging drying, microwave drying and infrared drying.

[0036] The embodiments of the present invention are applicable to the treatment of raw materials commonly used in the leather making field, such as bare skin, tanned leather and crust leather. Exemplarily, bare skin includes any one of delimed bare skin, softened bare skin, pickled bare skin and bare skin obtained by pickling-depickling and other processes; tanned leather includes any one of chrome tanned leather, aluminum tanned leather, zirconium tanned leather, zeolite tanned leather, multi-metal tanning agent tanned leather, vegetable tanned leather, aldehyde tanned leather, phenolic synthetic tanning agent tanned leather and active chlorine tanned leather; crust leather refers to crust leather obtained by performing at least one of the processes of retanning, dyeing and fatliquoring.

[0037] In order to better understand the technical solution provided by the present invention, the following uses a plurality of specific examples to illustrate the ultra-short process high-quality leather making method provided by the above-mentioned embodiment of the present invention, and performance testing.

[0038] In the following examples and comparative examples, the softness of leather was measured using a Gaotie GT-303 softness tester; the tear strength of leather was measured using a Gaotie AI-7000S servo-controlled computer system tensile testing machine.

[0039] Example 1 Chrome tanned leather was used as raw material and vacuum dried to obtain a leather blank with a moisture content of 21wt%; 0.1wt% Tween and 120wt% ethanol based on the weight of the chrome tanned leather were mixed, and the mixed solution of Tween and ethanol was used to infiltrate the tanned leather for 60 minutes. After extrusion, a leather blank infiltrated with Tween and ethanol was obtained; 10wt% dodecyltriethoxysilane was dissolved in 30wt% ethanol and brushed on the flesh surface of the leather blank for 60 minutes, and finally low-temperature infrared drying was carried out at 35°C to obtain high-quality leather.

[0040] The softness of the leather was measured to be 9.2 mm and the tear strength was 64.3 N / mm. The specific results are shown in Table 1.

[0041] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 only uses 120wt% ethanol to soak the tanned leather, and does not use Tween for soaking. The detailed process steps are as follows: Chrome tanned leather was used as raw material and vacuum dried to obtain a leather blank with a moisture content of 21wt%; 120wt% ethanol based on the weight of the chrome tanned leather was used to soak the tanned leather for 60 min, and after extrusion, an ethanol-soaked leather blank was obtained; 10wt% dodecyltriethoxysilane was dissolved in 30wt% ethanol and brushed on the flesh surface of the leather blank for 60min, and finally low-temperature infrared drying was carried out at 35°C to obtain leather.

[0042] The softness of the leather was measured to be 5.1 mm and the tear strength was 16.3 N / mm. The specific results are shown in Table 1.

[0043] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the moisture content of the crust obtained by vacuum drying in Comparative Example 2 is 15wt%, and the detailed process steps are: Chrome tanned leather is used as raw material and vacuum dried to obtain a leather blank with a moisture content of 15wt%; 0.1wt% Tween and 120wt% ethanol based on the weight of the chrome tanned leather are mixed, and the mixed solution of Tween and ethanol is used to infiltrate the tanned leather for 60 minutes, and after extrusion, a leather blank infiltrated with Tween and ethanol is obtained; 10wt% dodecyltriethoxysilane is dissolved in 30wt% ethanol and acted on the flesh surface of the leather blank for 60 minutes, and finally low-temperature infrared drying is carried out at 35°C to obtain leather.

[0044] The softness of the leather was measured to be 6.4 mm and the tear strength was 21.9 N / mm. The specific results are shown in Table 1.

[0045] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the moisture content of the crust obtained by vacuum drying in Comparative Example 3 is 45wt%, and the detailed process steps are: Chrome tanned leather is used as raw material and vacuum dried to obtain a leather blank with a moisture content of 45wt%; 0.1wt% Tween and 120wt% ethanol based on the weight of the chrome tanned leather are mixed, and the mixed solution of Tween and ethanol is used to infiltrate the tanned leather for 60 minutes, and after extrusion, a leather blank infiltrated with Tween and ethanol is obtained; 10wt% dodecyltriethoxysilane is dissolved in 30wt% ethanol and then brushed on the flesh surface of the leather blank for 60 minutes, and finally low-temperature infrared drying is carried out at 35°C to obtain leather.

[0046] The softness of the leather was measured to be 5.8 mm and the tear strength was 19.3 N / mm. The specific results are shown in Table 1.

[0047] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that, in Comparative Example 4, the raw material is not soaked with ethanol containing Tween and the excess ethanol is squeezed out, but Tween, ethanol and long-chain silane coupling agent are directly mixed at the same time to soak the raw material. The detailed process steps are as follows: Chrome tanned leather was used as raw material and vacuum dried to obtain a leather blank with a moisture content of 21wt%. 0.1wt% of Tween, 150wt% of ethanol and 10wt% of dodecyltriethoxysilane based on the weight of the chrome tanned leather were mixed and applied to the flesh surface of the leather blank for 120 min. Finally, low-temperature infrared drying was carried out at 35°C to obtain leather.

[0048] The softness of the leather was measured to be 4.6 mm and the tear strength was 13.9 N / mm. The specific results are shown in Table 1.

[0049] Table 1 Test results .

[0050] According to the test results of Example 1 and Comparative Examples 1-4, it can be seen that in Example 1, the moisture content of the leather blank is controlled within the range of 21wt%-40wt% by vacuum drying. After being infiltrated with a mixed solution of "Tween + ethanol", dodecyltriethoxysilane can fully penetrate into the leather blank, and low-temperature drying at an appropriate moisture content and 35°C can promote the full combination of silane and leather collagen, and finally obtain high-quality leather with a softness of 9.2 mm and a tear strength of 64.3 N / mm; although Comparative Example 1 controls the moisture content of the leather blank within the range of 21wt%-40wt% by vacuum drying, Tween is not used to infiltrate the leather blank, resulting in the silane being easily hydrolyzed into silanols with higher reaction activity when it meets water, and it is difficult to evenly penetrate into the leather blank. The leather softness obtained is only 5.1 mm and the tear strength is only 16.3 N / mm; in Comparative Example 2, the moisture content of the leather blank is controlled to 15wt% by vacuum drying. Although silane is easy to evenly penetrate into the leather blank at this low moisture content, it is difficult for silane to combine with leather collagen at 35°C, so the leather softness (6.4 mm) and tear strength (21.9N / mm) obtained in the end are also poor; in Comparative Example 3, the moisture content of the leather blank is controlled to 45wt% by vacuum drying. At this high moisture content, Tween cannot fully inhibit the hydrolysis of silane into silanol with high reactivity, resulting in the inability of silane to fully penetrate into the leather blank. Finally, the leather quality is still poor, with a softness of only 5.8 mm and a tear strength of only 19.3 N / mm; in Comparative Example 4, the raw material is not soaked with ethanol containing Tween and the excess ethanol is squeezed out, but Tween, ethanol and long-chain silane coupling agent are directly mixed at the same time to soak the raw material. This operation causes the long-chain silane coupling agent to be unable to be fully absorbed and evenly distributed in the leather. Finally, the leather softness (4.6mm) and tear strength (13.9 N / mm) is poor. It can be seen that only by controlling the moisture content of the leather blank within the range of 21wt%-40wt%, using the mixed solution of "Tween + ethanol" to first soak and squeeze out the excess ethanol, and then soaking with ethanol containing long-chain silane coupling agent, can the silane be evenly penetrated into the leather, and then fully combined with the leather collagen at a lower drying temperature, and finally high-quality leather can be obtained.

[0051] Example 2 Delimed bare hide is used as raw material and is hung and air-dried to obtain a leather blank with a moisture content of 40wt%; 0.1wt% Tween and 200wt% ethanol based on the weight of the delimed bare hide are mixed, and the mixed solution of Tween and ethanol is used to infiltrate the bare hide for 120 min, and after extrusion, a leather blank infiltrated with Tween and ethanol is obtained; 18wt% n-hexyltrichlorosilane is dissolved in 90wt% ethanol, and then applied to the flesh surface of the leather blank by drum rotation for 30 min, and finally low-temperature hanging and air-drying is carried out at 25°C to obtain high-quality leather.

[0052] The softness of the leather was measured to be 8.1 mm and the tear strength was 86.1 N / mm.

[0053] Example 3 Retanned leather was used as raw material and dried on a stretcher to obtain a leather with a moisture content of 30wt%; 0.5wt% Tween and 50wt% ethanol based on the weight of the retanned leather were mixed, and the mixed solution of Tween and ethanol was used to impregnate the leather for 5 minutes. After extrusion, a leather impregnated with Tween and ethanol was obtained; 2wt% octadecyltrimethoxysilane was dissolved in 10wt% ethanol and brushed on the flesh surface of the leather for 0.5 min, and finally low-temperature microwave drying was carried out at 50°C to obtain high-quality leather.

[0054] The softness of the leather was measured to be 8.2 mm and the tear strength was 58.7 N / mm.

[0055] Example 4 Softened bare hide is used as raw material and is hung and air-dried to obtain a leather blank with a moisture content of 40wt%; 0.1wt% Tween and 120wt% ethanol based on the weight of the softened bare hide are mixed, and the mixed solution of Tween and ethanol is used to infiltrate the bare hide for 60 minutes, and after extrusion, a leather blank infiltrated with Tween and ethanol is obtained; 10wt% n-hexylmethyldichlorosilane is dissolved in 10wt% ethanol, and the mixture is roller-coated on the flesh surface of the leather blank for 30 minutes, and finally the leather blank is hung and air-dried at 35°C to obtain high-quality leather.

[0056] The softness of the leather was measured to be 8.0 mm and the tear strength was 85.4 N / mm.

[0057] Example 5 Zirconium tanned leather was used as raw material and dried on a nail board to obtain a leather blank with a moisture content of 21wt%; 1wt% Tween based on the weight of the zirconium tanned leather and 200wt% ethanol were mixed, and the mixed solution of Tween and ethanol was used to infiltrate the tanned leather for 5 min, and after extrusion, a leather blank infiltrated with Tween and ethanol was obtained; 10wt% dodecyl(methyl)dimethoxysilane was dissolved in 30wt% ethanol and sprayed on the flesh surface of the leather blank for 0.5 min, and finally low-temperature infrared drying was carried out at 20°C to obtain high-quality leather.

[0058] The softness of the leather was measured to be 8.6 mm and the tear strength was 81.2 N / mm.

[0059] Example 6 Dyed crust leather was used as raw material and dried on a board to obtain a crust leather with a moisture content of 30wt%; 0.5wt% Tween and 50wt% ethanol based on the weight of the dyed crust leather were mixed, and the mixed solution of Tween and ethanol was used to impregnate the crust leather for 60 minutes, and after extrusion, a crust leather impregnated with Tween and ethanol was obtained; 18wt% octadecyltrichlorosilane was dissolved in 18wt% ethanol and then brushed on the flesh surface of the crust leather for 30 minutes, and finally low-temperature microwave drying was carried out at 50℃ to obtain high-quality leather.

[0060] The softness of the leather was measured to be 9.0 mm and the tear strength was 56.6 N / mm.

[0061] Example 7 Pickled bare hide is used as raw material and is hung and air-dried to obtain a leather blank with a moisture content of 40wt%; 0.1wt% Tween and 200wt% ethanol based on the weight of the pickled bare hide are mixed, and the mixed solution of Tween and ethanol is used to infiltrate the bare hide for 120 min, and after extrusion, a leather blank infiltrated with Tween and ethanol is obtained; 18wt% dodecyltrimethoxysilane is dissolved in 90wt% ethanol and sprayed on the flesh surface of the leather blank for 60 min, and finally low-temperature hanging and air-drying is carried out at 35°C to obtain high-quality leather.

[0062] The softness of the leather was measured to be 8.8 mm and the tear strength was 83.6 N / mm.

[0063] Example 8 Zeolite tanned leather was used as raw material and dried on a stretcher to obtain a leather blank with a moisture content of 21wt%; 0.5wt% Tween and 50wt% ethanol based on the weight of the zeolite tanned leather were mixed, and the mixed solution of Tween and ethanol was used to soak the tanned leather for 60 minutes, and after extrusion, a leather blank soaked with Tween and ethanol was obtained; 2wt% octadecyl (dimethyl) methoxysilane was dissolved in 10wt% ethanol and then roller-coated on the flesh surface of the leather blank for 0.5 min, and finally low-temperature hanging and infrared drying were carried out at 50°C to obtain high-quality leather.

[0064] The softness of the leather was measured to be 8.5 mm and the tear strength was 51.2 N / mm.

[0065] Example 9 The fatliquor crust leather was used as raw material, and it was hung and stretched to obtain a crust leather with a moisture content of 30wt%; 1wt% Tween and 120wt% ethanol based on the weight of the fatliquor crust leather were mixed, and the mixed solution of Tween and ethanol was used to impregnate the crust leather for 60 min, and after extrusion, a Tween-ethanol-impregnated crust leather was obtained; 10wt% octadecyltriethoxysilane was dissolved in 50wt% ethanol, and then applied to the flesh surface of the crust leather by drum rotation for 30 min, and finally low-temperature hung and microwave dried at 35℃ to obtain high-quality leather.

[0066] The softness of the leather was measured to be 9.1 mm and the tear strength was 54.7 N / mm.

[0067] Example 10 The bare hide obtained by the acid-deacidification process is used as raw material, and it is hung and air-dried to obtain a leather blank with a moisture content of 40wt%; 0.1wt% Tween and 200wt% ethanol based on the weight of the bare hide are mixed, and the mixed solution of Tween and ethanol is used to infiltrate the bare hide for 120 min, and after extrusion, a leather blank infiltrated with Tween and ethanol is obtained; 18wt% dodecyltrimethoxysilane is dissolved in 90wt% ethanol and sprayed on the flesh surface of the leather blank for 60 min, and finally it is hung and air-dried at 20℃ to obtain high-quality leather.

[0068] The softness of the leather was measured to be 8.4 mm and the tear strength was 83.5 N / mm.

[0069] Embodiment 11 Taking multi-metal tanning agent tanned leather as raw material, it was vacuum dried and stretched to obtain a leather blank with a moisture content of 30wt%; 0.5wt% Tween and 120wt% ethanol based on the weight of the multi-metal tanning agent tanned leather were mixed, and the mixed solution of Tween and ethanol was used to infiltrate the tanned leather for 5 min. After extrusion, a leather blank infiltrated with Tween and ethanol was obtained; 2wt% dodecyltrichlorosilane was dissolved in 10wt% ethanol and brushed on the flesh surface of the leather blank for 0.5 min, and finally low-temperature hanging and microwave drying were carried out at 50℃ to obtain high-quality leather.

[0070] The softness of the leather was measured to be 8.3 mm and the tear strength was 76.4 N / mm.

[0071] Example 12 The leather crust that has been retanned and fatliquored is used as raw material, and it is hung and dried on a board to obtain a leather crust with a moisture content of 21wt%; 1wt% of Tween and 50wt% of ethanol based on the weight of the leather crust are mixed, and the mixed solution of Tween and ethanol is used to impregnate the leather crust for 60 min, and after extrusion, a leather crust impregnated with Tween and ethanol is obtained; 10wt% of n-hexyltrimethoxysilane is dissolved in 30wt% of ethanol and sprayed on the flesh surface of the leather crust for 30 min, and finally low-temperature hanging and infrared drying are carried out at 35℃ to obtain high-quality leather.

[0072] The softness of the leather was measured to be 8.9 mm and the tear strength was 52.7 N / mm.

[0073] Embodiment 13 Vegetable tanned leather was used as raw material and was hung to dry, vacuum dried and collapsed to obtain a leather blank with a moisture content of 30wt%; 0.1wt% Tween and 50wt% ethanol based on the weight of the vegetable tanned leather were mixed, and the mixed solution of Tween and ethanol was used to soak the tanned leather for 5 min. After extrusion, a leather blank soaked with Tween and ethanol was obtained; 18wt% n-hexyltriethoxysilane was dissolved in 54wt% ethanol and brushed on the flesh surface of the leather blank for 60 min. Finally, low-temperature microwave drying was carried out at 20°C to obtain high-quality leather.

[0074] The softness of the leather was measured to be 8.1 mm and the tear strength was 50.1 N / mm.

[0075] Embodiment 14 The leather crust after retanning and dyeing was used as raw material, and it was hung to dry, vacuum and nailed to obtain a leather crust with a moisture content of 21wt%; 0.5wt% Tween and 200wt% ethanol based on the weight of the leather crust were mixed, and the mixed solution of Tween and ethanol was used to impregnate the leather crust for 120 min, and after extrusion, a leather crust impregnated with Tween and ethanol was obtained; 2wt% dodecyl (methyl) diethoxysilane was dissolved in 10wt% ethanol, and then roller-coated on the flesh surface of the leather crust for 0.5 min, and finally low-temperature infrared drying was carried out at 35℃ to obtain high-quality leather.

[0076] The softness of the leather was measured to be 8.4 mm and the tear strength was 55.2 N / mm.

[0077] Embodiment 15 Aldehyde tanned leather was used as raw material and vacuum dried to obtain a leather blank with a moisture content of 40wt%; 1wt% Tween and 120wt% ethanol based on the weight of the aldehyde tanned leather were mixed, and the mixed solution of Tween and ethanol was used to infiltrate the tanned leather for 60 min. After extrusion, a leather blank infiltrated with Tween and ethanol was obtained; 10wt% dodecyltriethoxysilane was dissolved in 50wt% ethanol and applied to the flesh surface of the leather blank by drum rotation for 30 min. Finally, low-temperature microwave drying was carried out at 50℃ to obtain high-quality leather.

[0078] The softness of the leather was measured to be 8.5 mm and the tear strength was 63.9 N / mm.

[0079] Example 16 The leather crust which has been retanned, dyed and fatliquored is used as raw material and vacuum dried to obtain a leather crust with a moisture content of 21wt%; 0.1wt% of Tween and 200wt% of ethanol based on the weight of the leather crust are mixed, and the mixed solution of Tween and ethanol is used to impregnate the leather crust for 5 min, and after extrusion, a leather crust impregnated with Tween and ethanol is obtained; 10wt% of dodecyltrimethoxysilane is dissolved in 30wt% of ethanol and sprayed on the flesh surface of the leather crust for 0.5 min, and finally low-temperature hanging drying is carried out at 30°C to obtain high-quality leather.

[0080] The softness of the leather was measured to be 8.8 mm and the tear strength was 53.8 N / mm.

[0081] Embodiment 17 Phenolic synthetic tanning agent tanned leather is used as raw material, which is hung and vacuum dried to obtain a leather blank with a moisture content of 30wt%; 1wt% Tween based on the weight of the phenolic synthetic tanning agent tanned leather and 120wt% ethanol are mixed, and the mixed solution of Tween and ethanol is used to infiltrate the tanned leather for 60 min, and after extrusion, a leather blank infiltrated with Tween and ethanol is obtained; 10wt% active chlorosilane is dissolved in 50wt% ethanol and then roller-coated on the flesh surface of the leather blank for 30 min, and finally low-temperature infrared drying is carried out at 30°C to obtain high-quality leather.

[0082] The softness of the leather was measured to be 8.6 mm and the tear strength was 54.2 N / mm.

[0083] Embodiment 18 Active chlorine tanned leather was used as raw material, and it was hung and dried on a board to obtain a leather blank with a moisture content of 21wt%; 0.5wt% Tween and 50wt% ethanol based on the weight of the active chlorine tanned leather were mixed, and the mixed solution of Tween and ethanol was used to infiltrate the tanned leather for 120min, and after extrusion, a leather blank infiltrated with Tween and ethanol was obtained; 18wt% octadecyltrimethoxysilane was dissolved in 54wt% ethanol and brushed on the flesh surface of the leather blank for 30min, and finally low-temperature hung and dried at 50℃ to obtain high-quality leather.

[0084] The softness of the leather was measured to be 8.9 mm and the tear strength was 67.5 N / mm.

[0085] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. An ultra-short process high-quality leather making method, characterized in that: Using bare leather, tanned leather or crust leather as raw material, pre-drying until the moisture content of the raw material is 21wt%-40wt%, impregnating with ethanol solution containing Tween, extruding, treating with long-chain silane coupling agent, and finally low-temperature drying; Wherein, based on the weight of the raw materials, the amount of Tween added is 0.1wt%-1wt%, and the amount of ethanol added is 50wt%-200wt%; The long-chain silane coupling agent is C n H 2n+1 (CH3) 3-m SiX m , n is an integer between 6 and 18, and X is a group that can be hydrolyzed into a silanol.

2. The ultra-short process high-quality leather making method according to claim 1, characterized in that: X includes any of a chloro group, a methoxy group and an ethoxy group.

3. The ultra-short process high-quality leather making method according to claim 1 or 2, characterized in that: The addition amount of the long-chain silane coupling agent is 2wt%-18wt% of the raw material weight.

4. The ultra-short process high-quality leather making method according to claim 1, characterized in that: The temperature of the low temperature drying is 20-50 °C.

5. The ultra-short process high-quality leather making method according to claim 1, characterized in that: The bare skin comprises any one of delimed bare skin, softened bare skin, pickled bare skin and bare skin obtained by pickling-depickling process.

6. The ultra-short process high-quality leather making method according to claim 1, characterized in that: The tanned leather comprises any one of chrome tanned leather, aluminum tanned leather, zirconium tanned leather, zeolite tanned leather, multi-metal tanning agent tanned leather, vegetable tanned leather, aldehyde tanned leather, phenolic synthetic tanning agent tanned leather and active chlorine tanned leather.

7. The ultra-short process high-quality leather making method according to claim 1, characterized in that: The crust leather is obtained by performing at least one of the processes of retanning, dyeing and fatliquoring.

8. The ultra-short process high-quality leather making method according to claim 1, characterized in that: The pre-dried raw material is infiltrated with an ethanol solution containing Tween for 5-120 min.

9. The ultra-short process high-quality leather making method according to claim 1, characterized in that: The method for treating with a long-chain silane coupling agent is as follows: applying an ethanol solution of the long-chain silane coupling agent to the flesh surface of the skin blank for 0.5-60 minutes by rotating a drum, brushing, rolling or spraying the solution.

10. Leather produced by the ultra-short process high-quality leather making method as claimed in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Novelmultifunctional ready-to-useaerogel composite for whole blood component protection and preparation method of novelmultifunctional ready-to-useaerogel composite

    CN106832439A

  • Aged cow leather softening agent and preparation method thereof

    CN108546790A

  • Preparation method of self-cleaning automobile interior composite leather

    CN110724771A

  • Super-hydrophobic modification method for substance containing leather collagen fibers, tanning-agent-free tanning method and leather product

    CN113061670A

  • Method for manufacturing metal-free leather through hydrophobic modification and manufactured leather product

    CN115747388A